2020
DOI: 10.1101/2020.01.14.906982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of geological and comparative phylogeographic data point to climate, not mountain uplift, as driver of divergence across the Eastern Andean Cordillera

Abstract: AimTo evaluate the potential role of the orogeny of the Eastern Cordillera (EC) of the Colombian Andes and the Mérida Andes (MA) of Venezuela as drivers of vicariance between populations of 37 tetrapod lineages co-distributed on both flanks, through geological reconstruction and comparative phylogeographic analyses.LocationNorthwestern South AmericaMethodsWe first reviewed and synthesized published geological data on the timing of uplift for the EC-MA. We then combined newly generated mitochondrial DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…This is mostly due to the rain shadow effect caused by the trade winds that come from the east [71]. In this case, the geographic variation in environment, i.e., higher humidity along the eastern slope relative to the western slope, is due to a potential geographic barrier, the Eastern Cordillera (but see [16]). Assuming uniformitarianism that the same processes have been acting on Rheobates across its 35 million year history (the estimated stem age reported by Muñoz-Ortiz et al [32]), a potential scenario would be that initial divergences are driven by local adaptation to environmental variation while obvious landscape features may arise secondarily, such as through the formation of valleys or mountain peaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mostly due to the rain shadow effect caused by the trade winds that come from the east [71]. In this case, the geographic variation in environment, i.e., higher humidity along the eastern slope relative to the western slope, is due to a potential geographic barrier, the Eastern Cordillera (but see [16]). Assuming uniformitarianism that the same processes have been acting on Rheobates across its 35 million year history (the estimated stem age reported by Muñoz-Ortiz et al [32]), a potential scenario would be that initial divergences are driven by local adaptation to environmental variation while obvious landscape features may arise secondarily, such as through the formation of valleys or mountain peaks.…”
Section: Discussionmentioning
confidence: 99%
“…The Andean uplift created valleys that may have promoted the diversification of a variety of organisms, for example, the wax palm genus Ceroxylon [10], the Ithomiini tribe of butterflies [11,12], the montane forest subspecies of the three-striped warbler bird, suggested to have occured by allopatric divergence [13], and the Adelomyia hummingbirds, whose divergence was coupled to Andean orogeny [14]. The rise of Andean peaks promoted lowland speciation in some groups, such as the Dendrocincla woodcreepers, through vicariance during the uplift [15], yet many lowland tetrapods appear to have been largely unaffected by Andean vicariance [16].…”
Section: Introductionmentioning
confidence: 99%
“…This is mostly due to the rain shadow effect caused by the trade winds that come from the east (Mark & Helmens, 2005). In this case the geographic variation in environment, i.e., higher humidity along the eastern slope relative to the western slope, is due to a potential geographic barrier, i.e., the Eastern Cordillera (but see Rodríguez-Muñoz et al, 2020). Assuming uniformitarianism, that the same processes have been acting on Rheobates across its 35 million year history [the estimated stem age reported by Muñoz-Ortiz et al (2015)], a potential scenario would be that initial divergences are driven by local adaptation to environmental variation while obvious landscape features may arise secondarily, such as through the formation of valleys or mountain peaks that secondarily act as barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies suggest that the Andean topography promotes genetic divergence and diversification in the tropics (Chaves et al, 2011;Gutiérrez-Pinto et al, 2012;Weir & Price, 2011), further investigation is needed to understand the origins of this diversity. In a recent pre-print, Rodríguez-Muñoz et al(2020) suggested that environment, rather than Andean uplift is the main factor explaining genetic divergence across lowland tetrapod species separated by the Eastern Andes. However, when invoking environment as a barrier, there are two factors to consider: one is the more typical assumption that the environment of the intervening region is what isolates pairs of populations, while the second possibility is the distinctiveness of the environment that characterizes the respective populations.…”
Section: Introductionmentioning
confidence: 99%
“…4.5 Ma, resulting in the current elevation of the Andes (Gregory-Woodzicki, 2000; Garzione et al , 2008; Mora et al , 2010; Hoorn et al , 2010). These dates are contested by geological studies of mainly coarse-grained deposits that suggest that the Eastern Cordillera was already well underway in Eocene times and nearly complete in the Late Miocene (>11 Ma) (Cooper et al , 1995; Montes et al , 2019; Rodríguez-Muñoz et al , 2020). Our divergence dating analysis results in Fig.…”
Section: Discussionmentioning
confidence: 99%